Digital Radiographic Assessment of Knee Joint Space with its Clinical Significances - `Mansur, Dil Islam; Karki, Subindra; Mehta, Dilip Kumar; Shrestha, Pragya; Maskey, Sunima (Birat Journal of Health Sciences, 2020)
Introduction: The knee joint space is seen on anteroposterior radiograph as a radiolucent area between lower end of femur and upper end of tibia which is an indirect way of evaluating the knee cartilage thickness. Objective: This study was aimed to determine the knee joint space in the medial and lateral compartments of the knee joint using digital radiograph. Methodology : This was cross-sectional study. It consisted of digital radiographs of knee joint of 320 individuals. The medial and lateral joint space width of each knee joint was measured using the scale in the computerized software. Results: The mean values for medial and lateral joint space widths were found to be 6.11±1.57 mm and 7.92±1.66 mm of the right knee joint respectively and 5.99±1.47 mm and 8.18±1.69 mm of the left knee joint respectively. In males, mean values for joint space widths were 6.37±1.58 mm on medial side and 8.21±1.67 mm on lateral side of the right knee; and 6.24±1.56 mm on medial side and 8.33±1.64 mm on lateral side of the left knee. In Females, these values were 5.89±1.53 mm on medial side and 7.66±1.62 mm on lateral side of the right knee; and 5.79±1.37 mm on medial side and 8.06±1.72 mm on lateral side of the left knee. Conclusions: It was concluded that the lateral joint space was greater than the medial joint space in both knees. The joint space widths were found to be reasonably constant with increasing age among studied population.